Healthcare ecosystems research in mental health: a scoping review of methods to describe the context of local care delivery - Mary Anne Furst; Coralie Gandré; Cristina Romero López-Alberca; Luis Salvador-Carulla (BMC Health Services Research, 2019)
Abstract Background Evidence from the context of local health ecosystems is highly relevant for research and policymaking to understand geographical variations in outcomes of health care delivery. In mental health systems, the analysis of context presents particular challenges related to their complexity and to methodological difficulties. Method guidelines and standard recommendations for conducting context analysis of local mental health care are urgently needed. This scoping study reviews current methods of context analysis in mental health systems to establish the parameters of research activity examining availability and capacity of care at the local level, and to identify any gaps in the literature. Methods A scoping review based on a systematic search of key databases was conducted for the period 2005–2016. A systems dynamics/complexity approach was adopted, using a modified version of Tansella and Thornicroft’s matrix model of mental health care as the conceptual framework for our analysis. Results The lack of a specific terminology in the area meant that from 10,911 titles identified at the initial search, only 46 papers met inclusion criteria. Of these, 21 had serious methodological limitations. Fifteen papers did not use any kind of formal framework, and five of those did not describe their method. Units of analysis varied widely and across different levels of the system. Six instruments to describe service availability and capacity were identified, of which three had been psychometrically validated. A limitation was the exclusion of grey literature from the review. However, the imprecise nature of the terminology, and high number of initial results, makes the inclusion of grey literature not feasible. Conclusion We identified that, in spite of its relevance, context studies in mental health services is a very limited research area. Few validated instruments are available. Methodological limitations in many papers mean that the particular challenges of mental health systems research such as system complexity, data availability and terminological variability are generally poorly addressed, presenting a barrier to valid system comparison. The modified Thornicroft and Tansella matrix and related ecological production of care model provide the main model for research within the area of health care ecosystems.